Permian 40Ar/39Ar ages for post-Variscan minor intrusions in the Iberian Range and Spanish Central System - G. PERINI; M.J. TIMMERMAN (Geologica Acta, 2009)
40Ar/39Ar dating of biotite from a calc-alkaline gabbro stock NW of Loscos in the Iberian Range yielded a slightly disturbed gas release spectrum. It has an early Permian, 288.5 ± 1.4 Ma total gas age, interpreted as the minimum emplacement age. The 40Ar/39Ar apparent age of the gabbro agrees with the Autunian stratigraphic age of related volcanic rocks. 40Ar/39Ar step-heating dating of amphibole phenocrysts from an alkaline camptonite dyke ca. 4 km SE of El Hoyo de Pinares in the Sierra Guadarrama sector of the Spanish Central System yielded a mid-Permian 264 ± 3 Ma plateau age, interpreted as the emplacement age. The age is indistinguishable from published 40Ar/39Ar amphibole ages for N-S trending camptonite dykes from the western, Sierra de Gredos segment of the Central System. This suggests that the camptonite dykes from both sectors belong to the same generation.